Monocrystalline silicon wafer suede structure of solar cell, texturing additive, texturing liquid, preparation method and solar cell

By using specific velvet-making additives and alkali solution on the surface velvet-making method on the single crystal silicon wafer after alkali casting of HJT batteries, a uniform pyramid morphology was formed, which solved the uneven deposition and uneven distribution of silver paste caused by excessive flatness of the surface. The problem of improving battery efficiency and cost-effectiveness.

CN119392380APending Publication Date: 2025-02-07CHANGZHOU SHICHUANG ENERGY CO LTD

Patent Information

Application Number
CN202411537894.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The surface of HJT batteries is too flat after alkali casting, resulting in uneven adsorption of velvet-making additives, affecting the formation of pyramid morphology, and thus affecting the uniformity of amorphous silicon thin film deposition and the printing effect of low-temperature spherical silver paste.

Method used

Using a velvet-making additive containing nucleating agent, velvet-making agent, tower surface etching agent, dispersing agent and defoaming agent, combined with an alkali solution, the surface velvet-making method forms a counterpart on the single crystal silicon wafer after alkali casting by the surface velvet-making method. Uniform pyramid morphology.

Benefits of technology

A uniform pyramid morphology is achieved on the surface of the silicon wafer after alkali casting. The spire is smooth, the height-to-wide ratio is low, and the tower surface is slightly guttered, which improves the uniformity of amorphous silicon thin film deposition and the printing effect of low-temperature spherical silver paste, reducing the silver Consumption and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392380A_ABST
    Figure CN119392380A_ABST
Patent Text Reader

Abstract

The invention provides a monocrystalline silicon wafer texturing structure of a solar cell, a texturing additive, a texturing solution, a texturing method and the solar cell. The texturing additive comprises 0.01-0.1 wt% of a nucleating agent, 0.03-0.5 wt% of a surface forming agent, 0.06-1 wt% of a tower surface etching agent, 0.1-1 wt% of a dispersing agent, 5-20 wt% of a defoaming agent and the balance of deionized water. The nucleating agent is benzene ring-containing polyoxyethylene ether, the tower surface etching agent is a vinyl pyrrolidone copolymer, the nucleating agent forms hydrogen bonds with Si-OH on the surface of an SDR silicon wafer by virtue of EO chain segments and benzene rings, and the hydrogen bonds are adsorbed on the flat surface of the silicon wafer to form nucleating points. And after the pyramid is formed, the nucleating agent at the spire is separated from the spire and loses protection on the spire, the surface forming agent can still protect the surface of the tower due to relatively strong adsorption, and the spire is slightly corroded, the spire is smooth and the height-width ratio of the pyramid is reduced due to continuous corrosion of alkali liquor. The tower surface etching agent is subjected to ester hydrolysis due to alkali and high temperature, so that the water solubility of the copolymer is improved; and the tower surface etching agent is adsorbed on the tower surface by virtue of the long chain segment of the copolymer, and is continuously corroded at the tower surface to form a slight gully type tower surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of silicon solar cells, and particularly relates to the field of silicon wafer texturing, specifically a single crystal silicon wafer texturing structure of a solar cell, a texturing additive, a texturing liquid, a texturing method and a solar cell. Background Art

[0002] HJT cells achieve high-efficiency power generation performance through the deposition and passivation process of intrinsic amorphous silicon thin films. In the manufacturing process of HJT cells, the morphology of the silicon wafer surface has a crucial impact on the quality of subsequent thin film deposition. On a flatter and evenly distributed pyramid velvet structure, the deposition process of amorphous silicon thin films can be carried out more evenly.

[0003] The low-temperature process used in HJT batteries requires a high content of low-temperature silver paste to ensure good conductivity, which directly leads to an increase in silver consumption and an increase in cost. Compared with high-temperature processes such as TOPCon, the silver consumption of HJT batteries is more than 30% higher, and the technical difficulty and price of low-temperature silver paste are both high. In order to reduce silver consumption and cost, fine grid technology has been proposed and applied. Fine grid can greatly reduce silver consumption, but fine grid needs to match a finer mesh. Since the particle size of the flaky silver powder in the conventional silver paste is 3-5um, its rolling and mesh passing properties are poor, so it is necessary to replace the flaky silver powder in the silver paste with spherical silver powder with a smaller particle size. However, the contact area between the spherical silver powder and the pyramid becomes smaller, and the adhesion is reduced. Under the action of gravity, the silver paste on the surface of the pyramid becomes thinner, resulting in uneven distribution of silver paste, poor contact, cold solder joints, and low welding tension, affecting battery efficiency and yield. In addition, since the current HJT battery uses alkaline polishing to remove the damaged layer in the silicon wafer pre-cleaning process to obtain a smoother surface. Through the alkaline polishing process, the surface of the silicon wafer becomes smoother. The flat surface is not conducive to the adsorption of texturing additives, resulting in uneven texture and high reflectivity, thereby reducing the photoelectric conversion efficiency.

[0004] Therefore, in order to deposit a more uniform amorphous silicon film and cope with fine grid, the requirements of HJT cells for the texture surface are: (1) forming a relatively uniform pyramid on the flat silicon wafer surface, with a smooth top, to improve the uniformity of amorphous silicon film deposition; (2) reducing the aspect ratio of the pyramid, making the pyramid "shorter"; the pyramid surface is rough to increase the silver paste contact area and friction.

[0005] In the prior art, there are several solutions for pyramid texturing on the surface of single crystal silicon: Patent document with publication number CN114759117A discloses a method for improving the uniformity of texturing of crystalline silicon cells, wherein the original diamond-cut silicon wafer is repeatedly washed and polished to obtain a smooth surface, and then texturing is performed, thereby reducing the consumption of liquid medicine and preparing pyramids with relatively uniform morphology. Publication number CN111455468A provides an additive for single crystal texturing, which can directly texturize to obtain a texturing sheet with a round and smooth velvet surface. The formed pyramid structure is no longer sharp, and the top and the tower surface have a certain roundness. However, the texturing additive is directly texturized on the original silicon wafer, and cannot match the polished silicon wafer, because the surface of the polished silicon wafer is smoother, which is not conducive to the adsorption and nucleation of the additive components. Publication number CN111326410A provides an anti-flower basket printing texturing liquid for HIT batteries and a texturing method thereof. The texturing liquid includes 0.1-5% of anti-basketball printing texturing additive, 0-0.5% of auxiliary texturing agent, 0.1-0.8% of pH buffer agent and the remainder is alkali solution according to weight percentage. It can prepare a pyramid with a corrugated tower surface, but the aspect ratio is not described. The silicon wafer used in CN111326410A is cleaned with dilute hydrochloric acid, and the surface flatness of the single acid washing process is low. At present, the pre-cleaning of silicon wafers of HJT batteries has been changed to alkaline polishing to remove the damaged layer to obtain a smoother surface. The anti-basketball printing texturing liquid will no longer be suitable for silicon wafers under the alkaline polishing process. Summary of the invention

[0006] Based on the above technical problems, the present invention proposes a velvet structure of a single crystal silicon wafer for a solar cell, a velvet additive, a velvet liquid, a preparation method and a solar cell, which are suitable for making the single crystal silicon wafer smoother after damage by alkali polishing, and prepare a relatively uniform pyramid morphology with a smooth top, a low aspect ratio and a slightly grooved tower surface, so as to improve the uniformity of amorphous silicon thin film deposition and the low-temperature spherical silver paste printing effect.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: A velvet structure of a single crystal silicon wafer of a solar cell, characterized in that the velvet structure is a pyramid structure, the bottom edge of the pyramid structure is a, the height from the top to the bottom of the pyramid structure is h, and the ratio of a to h ranges from 55% to 65%.

[0008] A texturing additive for single crystal silicon wafers used for preparing the texturing structure of the single crystal silicon wafer, characterized in that the ingredients and content of the texturing additive for single crystal silicon wafers are as follows: 0.01~0.1wt% of nucleating agent, 0.03~0.5wt% of surface agent, 0.06~1wt% of tower surface etchant, 0.1~1wt% of dispersant, 5~20wt% of degassing agent, and the balance is deionized water; the nucleating agent is a polyoxyethylene ether containing a benzene ring, and the EO number is between 5 and 10; the tower surface etchant is a copolymer of vinyl pyrrolidone.

[0009] Furthermore, the benzene ring-containing polyoxyethylene ether is selected from one or more of bisphenol A polyoxyethylene ether, nonylphenol polyoxyethylene ether, octylphenyl polyoxyethylene ether, distyrylphenol polyoxyethylene ether, and tristyrylphenol polyoxyethylene ether; the molecular weight Mw of the benzene ring-containing polyoxyethylene ether is 2000-5000.

[0010] Furthermore, the copolymer of vinyl pyrrolidone is selected from one or two of poly(vinyl pyrrolidone-vinyl acetate) and poly-tert-butyl acrylate-poly(N-vinyl pyrrolidone).

[0011] Furthermore, the monomer vinyl pyrrolidone accounts for 60% to 80% of the copolymer of vinyl pyrrolidone.

[0012] Furthermore, the surface forming agent is selected from one or more of ethoxylated polyethyleneimine, polyethylene glycol-polyglutamic acid-polyethyleneimine, polyethyleneimine-polyethylene glycol-trifluoromethanesulfonyl.

[0013] Furthermore, the dispersant is an anionic amino acid surfactant, and the anionic amino acid surfactant is selected from one or more of sodium lauroyl sarcosinate, sodium lauroyl lysine, sodium lauroyl glutamate, sodium cocoyl glycinate, and sodium methyl cocoyl taurate.

[0014] Furthermore, the defoaming agent is a natural high molecular weight water-soluble polysaccharide, selected from one or more of dextran, carrageenan, xanthan gum, tamarind gum, and sodium alginate.

[0015] A single crystal silicon wafer texturing liquid for preparing the single crystal silicon wafer texture structure, characterized in that: it includes the single crystal silicon wafer texturing additive, the mass ratio of the texturing additive to the alkaline solution is 0.2~2:100; the alkaline solution is 0.5~1.5wt% sodium hydroxide or potassium hydroxide aqueous solution.

[0016] The method for preparing the textured structure of a single crystal silicon wafer is characterized by comprising the following steps: (1) Silicon wafer alkaline polishing: Clean the dirt on the surface of the original silicon wafer, use alkaline solution to polish and remove the mechanical damage layer on the surface of the original silicon wafer to obtain a flat surface; then use NaOH and H 2 O 2 The mixed solution forms an oxide layer on the surface of the silicon wafer, which is then washed with clean water and named SDR silicon wafer; (2) Preparation of texturing liquid: the texturing additive and the alkaline solution are uniformly mixed in a mass ratio of 0.2 to 2:100 to prepare a texturing liquid; (3) Texturing: Immerse the SDR silicon wafer in the texturing liquid for surface texturing. The texturing temperature is 75~80℃ and the time is 8~10 minutes.

[0017] A solar cell is characterized by being made of a single crystal silicon wafer having the single crystal silicon wafer texture structure.

[0018] In the texturing additive of the present invention, the nucleating agent is a polyoxyethylene ether containing a benzene ring. The nucleating agent can form hydrogen bonds with Si-OH on the surface of the SDR silicon wafer after oxidation treatment by means of EO segments and benzene rings, and then adsorb on the flat silicon wafer surface to form nucleation points; at the same time, since the molecular weight of the nucleating agent is between 2000 and 5000, the molecular weight range is relatively concentrated, and the molecular segments of the nucleating agent are close, a relatively uniform velvet surface can be formed. However, since the EO number is between 5 and 10, the polyoxyethylene ether segment is relatively short, and the overall adsorption force is weak. As the pyramid is slowly formed, the contact area between the nucleating agent and the silicon wafer at the top of the tower becomes smaller, causing the nucleating agent to detach from the top of the tower and lose its protective effect on the top of the tower. However, the surface agent still has the effect of protecting the tower surface due to its strong adsorption. The continuous corrosion of the alkali solution causes the top of the tower to be slightly corroded, the top of the tower is smooth, the pyramid becomes shorter, and the aspect ratio is reduced.

[0019] The tower surface etchant is a copolymer of vinyl pyrrolidone. It is selected from one or two of poly (vinyl pyrrolidone-vinyl acetate) and poly tert-butyl acrylate-poly (N-vinyl pyrrolidone). In the texturing solution, the above two copolymers will cause ester hydrolysis due to alkali and high temperature, increasing the water solubility of the copolymer. After the texturing tower surface is formed, the tower surface etchant is adsorbed on the formed tower surface by the long chain segment of the copolymer. Since the copolymer has strong hydrophilicity and weak inhibition reaction, the alkali solution will continue to corrode the tower surface, thereby forming a slightly grooved tower surface.

[0020] Compared with the prior art, the present invention has the following advantages: The texturing additive of the present invention can be applied to the pre-cleaning process of the current HJT battery. After the silicon wafer is damaged by the alkaline polishing method, the texturing additive of the present invention can prepare a uniform velvet structure on the flat silicon wafer surface with a reflectivity of 10% to 12%; The texturing additive of the present invention can increase the roughness of the pyramid surface, prepare a relatively uniform pyramid morphology with a smooth top, low aspect ratio, and slightly grooved tower surface, so that the pyramid structure is flatter. This morphology is used to match HJT batteries, which is conducive to the deposition of uniform amorphous silicon thin films. For the fine grid process, this morphology can improve the problem of uneven silver paste distribution caused by gravity, improve the printing effect of low-temperature spherical silver paste, and increase the contact area, adhesion, and welding tension of the silver paste, thereby enhancing the conductivity and improving the battery efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a top view of the velvet surface of the silicon wafer obtained in Example 1.

[0022] Figure 2 This is a cross-sectional view of the textured surface of the silicon wafer obtained in Example 1.

[0023] Figure 3 This is a top view of the velvet surface of the silicon wafer obtained in Example 2.

[0024] Figure 4 This is a cross-sectional view of the textured surface of the silicon wafer obtained in Example 2.

[0025] Figure 5 It is a top view of the velvet surface of the silicon wafer obtained in the comparative example.

[0026] Figure 6 This is a cross-sectional view of the textured surface of the silicon wafer obtained in the comparative example. DETAILED DESCRIPTION

[0027] The following is a further non-limiting detailed description of the technical solution of the present invention in conjunction with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0028] (1) Preparation of texturing additives: Prepare the texturing additives according to the following mass percentages: 0.02% bisphenol A polyoxyethylene ether, 0.04% ethoxylated polyethyleneimine, 0.08% poly(vinyl pyrrolidone-vinyl acetate), 0.1% sodium lauroyl sarcosinate, 5% dextran, and the remainder is deionized water; mix well and dissolve completely to obtain the texturing additive.

[0029] (2) Silicon wafer preparation: Step 1: Place the 182mm*182mm M10 original silicon wafer into 0.5wt% NaOH and 3wt% H 2 O 2The mixed solution is kept at 65°C for 150 seconds for pre-cleaning to remove dirt on the surface of the original silicon wafer.

[0030] Step 2: The original silicon wafer is then placed in an alkaline solution with a concentration of 2wt% NaOH and maintained at 70°C for 3-5 minutes for polishing. The weight loss is controlled at 0.4-0.6g to remove the mechanical damage layer on the surface of the original silicon wafer and obtain a flat surface.

[0031] Step 3: Perform the operation of step 1 on the polished silicon wafer to form an oxide layer on the surface of the silicon wafer to facilitate subsequent texturing.

[0032] Soak the silicon wafer after step 3 in clean water. The obtained silicon wafer is named SDR silicon wafer and is ready for use. The silicon wafer used for subsequent texturing is the same.

[0033] (3) Preparation of texturing liquid: prepare a 1 wt% NaOH solution in a texturing tank, add the texturing additive prepared in step (1) into the alkaline solution at a mass ratio of 0.5:100 and mix well to obtain a texturing liquid.

[0034] (4) Texturing: Put the SDR silicon wafer into the texturing liquid for surface texturing at 75℃ for 10 minutes. Take out the silicon wafer after texturing, clean the surface residue, dry it and then test the reflectivity. The average reflectivity is 10.8%.

[0035] Observe the top view and cross-sectional morphology of the silicon wafer texture. Figure 1 , Figure 2 As shown in the figure, the height and width of the cross-section pyramid are 965.40nm and 1.65μm respectively. Relatively uniform pyramids are formed on the surface of the silicon wafer, with smooth tops and no microstructures, slight grooves on the pyramid surface, and a pyramid height-to-width ratio of 58%. Example 2

[0036] (1) Preparation of texturing additives: Prepare according to the following mass percentages: 0.01% tristyrylphenol polyoxyethylene ether, 0.06% polyethylene glycol-polyglutamic acid-polyethyleneimine, 0.1% poly(tert-butyl acrylate)-poly(N-vinyl pyrrolidone), 0.2% sodium methyl cocoyl taurate, 10% tamarind gum, and the rest is deionized water. Mix well and dissolve completely to obtain the texturing additive.

[0037] (2) Silicon wafer preparation, same as in Example 1.

[0038] (3) Preparation of texturing solution: Prepare a 1.5 wt% NaOH solution in a texturing tank, add the texturing additive prepared in step (1) into the alkaline solution at a mass ratio of 0.75:100 and mix well to obtain a texturing solution.

[0039] (4) Texturing: Put the SDR silicon wafer into the texturing liquid for surface texturing at 80℃ for 10 minutes. Take out the silicon wafer after texturing, clean the surface residue, dry it and then test the reflectivity. The average reflectivity is 11.0%.

[0040] Observe the top view and cross-sectional morphology of the silicon wafer texture. Figure 3 , Figure 4 As shown, the height and width of the cross-sectional pyramid are 838.37 nm and 1.35 μm respectively. A relatively uniform pyramid is formed on the surface of the silicon wafer in this embodiment, with a smooth pyramid tip and no microstructure, slight grooves on the pyramid surface, and a pyramid height-to-width ratio of 62%. Comparative Example

[0041] (1) Textile making additive: Changzhou Shichuang Energy Co., Ltd., product model: HJ21.

[0042] (2) Silicon wafer preparation: same as in Example 1.

[0043] (3) Preparation of texturing liquid: Prepare 1.5 wt% NaOH solution in a texturing tank, add HJ21 texturing additive into the alkaline solution at a mass ratio of 0.75:100 and mix well to obtain texturing liquid.

[0044] (4) Texturing: Put the SDR silicon wafer into the texturing liquid for surface texturing at 80℃ for 10 minutes. Take out the silicon wafer after texturing, clean the surface residue, dry it and then test the reflectivity. The average reflectivity is 10.3%.

[0045] Observe the top view and cross-sectional morphology of the silicon wafer texture. Figure 5 , Figure 6 As shown, the height and width of the cross-section pyramid are 918.63 nm and 1.30 μm respectively. The silicon wafer of this comparative example forms a relatively uniform pyramid on its surface, with a rough pyramid tip and a barbed microstructure, and a smooth pyramid surface, with a pyramid height-to-width ratio of 70%.

[0046] The velvet sheets obtained in the above-mentioned embodiments and comparative examples were tested using a NXT Helios-rc reflectivity tester. The front and back sides of the silicon wafer were tested separately, and then the average reflectivity of the front and back sides was calculated. By comparing the embodiments and comparative examples, it can be obtained that the pyramid tip obtained in the comparative example is rough, has a barbed microstructure, the pyramid surface is smooth, and the aspect ratio of the pyramid is 70%. The pyramid tips obtained in Examples 1 and 2 are smooth, have no microstructure, have slight grooves on the pyramid surface, and the aspect ratio of the pyramid is between 55 and 65%. Due to the reduction of microstructures at the tip of the pyramid, the reflectivity is higher than that of the comparative example.

[0047] The efficiency of the additives in Examples 1 and 2 and the comparative example was compared in the HJT production line. During the test, the production line efficiency was stable, a single variable was kept, only the additive was changed, and the others remained unchanged. Table 1 is a comparison of the efficiency of Examples 1 and 2 in the HJT production line with the comparative example, where the comparison method is based on the comparative example as the baseline, the improvement percentage is represented by "+", and the reduction percentage is represented by "-".

[0048] Table 1 Comparison of the efficiency of HJT cells corresponding to the texturing additives Types of Texturing Additives ΔEta ΔUoc ΔIsc ΔFF Example 1 +0.04% +0.7mV -0.8mA +0.06 Example 2 +0.03% +1.2mV -12.2mA +0.09 According to the efficiency comparison results, compared with the comparative example, the texturing additives described in Example 1 and Example 2 improve the conversion efficiency Eta, open circuit voltage Uoc and fill factor FF of the HJT battery.

[0049] The main influencing factor of the open circuit voltage Uoc in a single crystal cell is the interface recombination between the surface of the single crystal silicon pyramid and the amorphous silicon film and the silver paste. The main influencing factor of the filling factor FF is the interface contact. The better the contact, the higher the FF. Since the pyramids prepared in Example 1 and Example 2 have relatively uniform morphology, smooth spires, slight grooves on the tower surface, and reduced aspect ratio, the recombination at the interface with the amorphous silicon film is reduced, the contact effect between the pyramid and the amorphous silicon film and the silver paste is improved, the open circuit voltage Uoc and the filling factor FF of the HJT cell are improved, and the purpose of improving the cell efficiency is achieved.

[0050] Regarding the test results of the reduction in the short-circuit current Isc of the HJT battery corresponding to Examples 1 and 2 of the present invention, it is because the reflectivity of the pyramid-shaped surface prepared by the texturing additive described in the present invention is higher than that of the control example, which leads to a slight reduction in the short-circuit current Isc.

[0051] Finally, it should be pointed out that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents, and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A single crystal silicon wafer textured structure for a solar cell, characterized in that: The velvet structure is a pyramid structure, the bottom side of the pyramid structure is a, the height from the top to the bottom of the pyramid structure is h, and the ratio of a to h is in the range of 55% to 65%.

2. A single crystal silicon wafer texturing additive for preparing the single crystal silicon wafer texture structure according to claim 1, characterized in that: The composition and content of the single crystal silicon wafer texturing additive are as follows: 0.01~0.1wt% nucleating agent, 0.03~0.5wt% surface forming agent, 0.06~1wt% tower surface etchant, 0.1~1wt% dispersant, 5~20wt% defoaming agent, and the balance is deionized water; the nucleating agent is a benzene ring-containing polyoxyethylene ether with an EO number between 5 and 10; the tower surface etchant is a copolymer of vinyl pyrrolidone.

3. The single crystal silicon wafer texturing additive according to claim 2, characterized in that: The benzene ring-containing polyoxyethylene ether is selected from one or more of bisphenol A polyoxyethylene ether, nonylphenol polyoxyethylene ether, octylphenyl polyoxyethylene ether, distyrylphenol polyoxyethylene ether, and tristyrylphenol polyoxyethylene ether; the molecular weight Mw of the benzene ring-containing polyoxyethylene ether is 2000-5000.

4. The single crystal silicon wafer texturing additive according to claim 2, characterized in that: The copolymer of vinyl pyrrolidone is selected from one or two of poly(vinyl pyrrolidone-vinyl acetate) and poly-tert-butyl acrylate-poly(N-vinyl pyrrolidone).

5. The single crystal silicon wafer texturing additive according to claim 2, characterized in that: The monomer vinyl pyrrolidone accounts for 60% to 80% of the copolymer of vinyl pyrrolidone.

6. The single crystal silicon wafer texturing additive according to claim 2, characterized in that: The surface forming agent is selected from one or more of ethoxylated polyethyleneimine, polyethylene glycol-polyglutamic acid-polyethyleneimine, polyethyleneimine-polyethylene glycol-trifluoromethanesulfonyl.

7. The single crystal silicon wafer texturing additive according to claim 2, characterized in that: The dispersant is an anionic amino acid surfactant, and the anionic amino acid surfactant is selected from one or more of sodium lauroyl sarcosinate, sodium lauroyl lysine, sodium lauroyl glutamate, sodium cocoyl glycinate, and sodium methyl cocoyl taurate.

8. The single crystal silicon wafer texturing additive according to claim 2, characterized in that: The defoaming agent is a natural high molecular weight water-soluble polysaccharide, selected from one or more of dextran, carrageenan, xanthan gum, tamarind gum and sodium alginate.

9. A single crystal silicon wafer texturing liquid for preparing the single crystal silicon wafer texture structure according to claim 1, characterized in that: The invention comprises the texturing additive for single crystal silicon wafers according to any one of claims 2 to 8, wherein the mass ratio of the texturing additive to the alkaline solution is 0.2 to 2:100; and the alkaline solution is a 0.5 to 1.5 wt % aqueous solution of sodium hydroxide or potassium hydroxide.

10. The method for preparing the textured structure of a single crystal silicon wafer according to claim 1, characterized in that: The following steps are involved: (1) Alkaline polishing of silicon wafers: Clean the dirt on the surface of the original silicon wafer, use alkaline solution to polish and remove the mechanical damage layer on the surface of the original silicon wafer to obtain a flat surface; then use a mixed solution of NaOH and H2O2 to form an oxide layer on the surface of the silicon wafer, and then wash it with clean water. The resulting silicon wafer is named SDR silicon wafer; (2) Preparation of texturing liquid: the texturing additive and the alkaline solution are uniformly mixed in a mass ratio of 0.2 to 2:100 to prepare a texturing liquid; (3) Texturing: Immerse the SDR silicon wafer in the texturing liquid for surface texturing. The texturing temperature is 75~80℃ and the time is 8~10 minutes.

11. A solar cell, characterized in that: It is made of a single crystal silicon wafer having the single crystal silicon wafer texture structure as claimed in claim 1.

Citation Information

Patent Citations

  • Basket mark prevention texturing solution for HIT battery and texturing method of basket mark prevention texturing solution

    CN111326410A

  • Additive for single crystal texturing and application thereof

    CN111455468A

  • Method for improving texturing uniformity of crystalline silicon cell

    CN114759117A

Cited By

  • Textured structure of combined passivation back contact battery and preparation method of textured structure

    CN119789617A

  • Texturing agent composition and texturing liquid

    CN119980479A